Safety Hat for Blind People - Yahaya, Afiq Irfan; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2023)
People who are visually handicapped or blind find it challenging to travel alone, mostly because they are less aware of their surroundings and unable to feel potential risks. These might endanger themselves. Thus, this work proposed a Safety Hat for Blind People to assist them in performing their daily routines such as walking the dog and buying groceries, only to name a few. The safety hat is made up of three major systems: an obstacle avoidance system, a health monitoring system, and a rain monitoring system, all of which are connected to an Arduino Mega 2560. The obstacle avoidance system, which makes use of four pairs of ultrasonic sensors, shall be activated to alert the user of approaching obstacles from the front, back, left, or right side. Based on experiments, the obstacle avoidance system may detect an obstruction within 100 cm. The user's pulse rate and amount of oxygen (SpO2) can be assessed by the health monitoring system, which employs a pulse oximeter and heart rate sensor, and the results are displayed on the LCD display attached to the safety hat. A buzzer that signals a high pulse rate shall be activated if the measured pulse rate exceeds 100 bpm. The rain monitoring system, on the other hand, uses a rain sensor module to detect the presence of water and uses a buzzer to alert the user. Based on the outcomes of the experiments, this Safety Hat for Blind People shall provide a secure environment for them to lead their daily life normally without any sense of danger.